Characteristics of Donghe Sandstone Transport Conductor in Hudson Oilfield, Tarim Basin and Its Oil and Gas Control Effect - Haitao Zhao; Dongsheng Wu; Kaiyu Wang; Shan Jiang (Applied Sciences)
The Hudson Oilfield’s Donghe sandstone reservoir has multiple independent oil–water systems. The complex oil–water relationship is mainly due to reservoir heterogeneity, especially the sealing and shielding effects of interlayers. This paper uses methods like well logging and test well data interpretation, seismic impedance inversion, and the simulation of oil and gas preferential migration paths. It analyzes and quantifies parameters related to sand layer oil content, physical properties, and the development degree of interbedded layers using small layers as units. Sandstone horizontal transportability has three types. Type I matches structural forms to form preferential migration paths. Type II transportability has enclosed sand bodies that obstruct oil and gas flow and change their migration paths. Unevenly distributed calcareous interbedded layers are the main controlling factor for vertical sand body transportability. Locally continuous cemented calcareous interbedded layers can form the base of a dome-shaped pinch-out lithologic trap in sandstone. The closure area of the trap is controlled by the pinch-out line of sandstone and the distribution of continuous interbedded layers together.